PRICE REGISTRATION AT EVENTS PT. PACTOCONVEXNIAGATAMA CASE STUDY DASABAKTI SMI 2019 &GROUP MEETING EGMONT 2019 - Salsabila, Fairuz; Ferezagia, Debrina Vita (Journal of Indonesian Tourism and Policy Studies, 2019)
This Study discusses a case study of the participants registration from two events managed by PT. Pactoconvex Niagatama, There are Dasabakti PT. SMI 2019 event that used the manual registration system, and the Egmont Group Meetings 2019 Event that used online registration system. The results of this case study are that the online registration system has better and safer in handling participants data and more efficient than the manual registration system. In addition, the author also wrote about the function of registration in an event and which registration methods are commonly used at an event.